Could KIM-1 and NGAL levels predict acute kidney injury after paracentesis? – preliminary study. Issue 1 (1st January 2020) - Pietrukaniec, Marta; Migacz, Maciej; Żak-Gołąb, Agnieszka; Olszanecka-Glinianowicz, Magdalena; Chudek, Jerzy; Duława, Jan; Holecki, Michał
Abstract: Background: Kidney dysfunction is a common complication in patients with severe liver cirrhosis. There is a need for discovery and validation of novel biomarkers for earlier AKI detection. The aim of this study was to determine if tubular injury markers: NGAL and KIM-1 could be helpful in the early diagnosis of AKI in patients undergoing therapeutic paracentesis. Methods: This preliminary study included 24 adult patients diagnosed with liver cirrhosis who had been hospitalized due to massive ascites requiring paracentesis. Pre- and post-paracentesis plasma samples were taken from each patient and biomarkers were measured. Results: Before paracentesis, the levels of serum and urinary NGAL were similar between patients and controls; while urinary KIM-1 was markedly increased in liver cirrhotic patients (0.76 vs. 0.24 ng/ml; respectively). Although urinary NGAL levels in AKI patients were 5-time greater than in non-AKI subgroup, the difference did not reach statistical significance (13.2 vs 1.5 pg/mL, p  = 0.06). Serum NGAL level, post-procedure, was 3 times greater in AKI subgroup. Conclusion: Kidney injury markers, especially serum NGAL, may be useful for the early detection of AKI. However, further research is required to determine if biomarkers of kidney injury may help identify patients with cirrhosis who would most likely benefit from early AKI prevention and treatment.